KAJIAN DAMPAK PEMEKARAN WILAYAH TERHADAP KINERJA EKONOMI DAERAH PESISIR DI PROVINSI BENGKULU - Arianti, Nyayu Neti; Cahyadinata, Indra (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2014)
The aims of this research were to analyze the impact of ECGI, WELFI, POVEI are used to regional divisions on coastal regions in Bengkulu Province to 1) economic performances before and after the divisions, and 2) economic performances of Core Region, New Autonomus Region, and both after the divisions. The results of this research : 1) the differential t test analyses of economic performance indicators in coastal region of Bengkulu Province showed that the economic growth before and after the divisions were not different, the GDP per capita after the divisions was higher than before, and the poverty indexes were same between before and after the divisions, and 2) the economic performance after the divisions of coastal region in Bengkulu Province could be explained that the economic growth of the Core Region was the highest and stable whereas the economic growth of the New Autonomous Region was the lowest and tend to unstable, the highest GDP per capita was occured on the Core Region and the lowest one was on the New Autonomous Region, while the lowest poverty index was on the Core Region and the highest one was on the New Autonomous Region.